Interrelations among expectancies, task values, and perceived costs in undergraduate biology achievement - Perez, Tony; Dai, Ting; Kaplan, Avi; Cromley, Jennifer G.; Brooks, Wanda D.; White, Arianna C.; Mara, Kyle R.; Balsai, Michael J. (Learning and individual differences, 2019)
Expectancy-value theory highlights the roles of students' expectancies, task values, and perceived costs in their motivation and achievement. While ample research has highlighted the positive associations of expectancy beliefs and task values with academic achievement, research on students' perceived costs is in its infancy. We investigated the temporal interrelations among expectancies, task values and different types of perceived cost, the role of these constructs in biology achievement, and the role of perceived costs as a moderator in the relations of expectancy beliefs to biology achievement. A cross-lagged path analysis of semester-long data from 234 undergraduate biology students pointed to variable relations among expectancies, task values, perceived costs, and biology achievement. For example, while early expectancy beliefs related to later attainment and interest value, early task values and perceived costs did not relate to later expectancy beliefs. Furthermore, early attainment value related to later effort and opportunity cost. Expectancy beliefs and effort and opportunity cost in biology were associated with final biology grade. Finally, effort cost moderated the relations between expectancy beliefs and students' final grades. These findings provide evidence for the dynamic relations among perceived costs, task values, and expectancy beliefs over a semester and point to the interplay between expectancies and perceived costs in their relation to academic achievement in science. •Early expectancy beliefs and utility value positively related to end-of-semester attainment value.•Early-semester expectancy beliefs also related to end-of-semester interest value.•Early-semester attainment value negatively related to end-of-semester effort cost and opportunity cost.•End-of-semester expectancy beliefs, effort cost, and opportunity cost related to final biology grade.•Effort cost moderated the relations between expectancy beliefs and biology achievement.